2021
DOI: 10.1148/radiol.2021210213
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial or Pulmonary Artery Chemoembolization for Unresectable and Unablatable Lung Metastases: A Phase I Clinical Trial

Abstract: M ost patients with lung metastases have unresectable disease (1). Patients with unresectable and unablatable lung metastases have poor survival and limited treatment options when the metastases stop responding to systemic chemotherapy (2).Transarterial chemoembolization (TACE) of the pulmonary or bronchial arteries is an emerging treatment option for large and multifocal lung tumors (Table E1 [online]). Like the liver, the lung has a dual blood supply. However, unlike liver tumors, which are mostly supplied b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 31 publications
(17 reference statements)
0
18
0
4
Order By: Relevance
“…It has been reported that local therapeutic efficacy of BACE is 2-6 times that of intravenous chemotherapy [11]. BACE can maximize the therapeutic effect with a relatively small amount of chemotherapeutic drugs [12]. This work then investigated the use and the effi-cacy of BACE combined with 125I seed implantation in advanced NSCLC therapy based on the medical database.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that local therapeutic efficacy of BACE is 2-6 times that of intravenous chemotherapy [11]. BACE can maximize the therapeutic effect with a relatively small amount of chemotherapeutic drugs [12]. This work then investigated the use and the effi-cacy of BACE combined with 125I seed implantation in advanced NSCLC therapy based on the medical database.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, drug delivery technology for microspheres has developed rapidly and clinical trials related to it have been widely conducted worldwide. Microsphere delivery systems have shown exciting potential for application in humans, mainly focused on the control and treatment of several diseases, including cancer ( Vilgrain et al, 2017 ; Chow et al, 2018 ; Ricke et al, 2019 ; Edeline et al, 2020 ; Boas et al, 2021 ; Garin et al, 2021 ), diabetes ( Bode et al, 2015 ; Rosenstock et al, 2015 ; Seaquist et al, 2020 ), and osteoarthritis ( Conaghan et al, 2018 ; Kraus et al, 2018 ). We can fully expect breakthrough efficacy and advances in these diseases from microsphere formulations.…”
Section: Clinical Transformation and Challenges Of Microspheresmentioning
confidence: 99%
“…These studies should be interpreted with caution, as most are small and retrospective, and mild worsening of pulmonary function was reported in a small, prospective trial of TACE. 4 Regarding bleeding complications, TAE is a standard treatment option for most tumor-related indications. Preoperative TAE of tumors to control intraoperative blood loss has been described in case reports for a wide variety of benign and malignant chest neoplasms.…”
Section: Chest Tumors: Transarterial Embolization To Manage Symptoms ...mentioning
confidence: 99%
“…These studies should be interpreted with caution, as most are small and retrospective, and mild worsening of pulmonary function was reported in a small, prospective trial of TACE. 4…”
Section: Chest Tumors: Transarterial Embolization To Manage Symptoms ...mentioning
confidence: 99%
See 1 more Smart Citation